Shear strength parallel to grain with distinct ray orientation on four Brazilian wood species - Longui, Eduardo Luiz; Pires, Gabriela Trindade; Ballarin, Adriano Wagner [UNESP]; Machado, José Arimatéia Rabelo (Springer Nature, 2017)
Ray orientation (perpendicular, parallel and diagonal) was compared with respect to shear strength parallel to grain and specific gravity in four Brazilian wood species. Higher absolute strengths occurred with ray oriented perpendicular to the shear plane, and lower ones for parallel orientation for almost all species. In particular, specimens with parallel ray orientation to shear plane did not differ statistically from shear values when compared to specimens having perpendicular and diagonal orientation to shear plane.